DEPENDENCE OF SULFUR FUGACITY ON THE COMPOSITION OF PHASE ASSOCIATIONS IN THE FE-FES-NIS-NI SYSTEM AT 873 K - Kosyakov V.I.; Shestakov V.A.; Sinyakova E.F. (My University, 2003)
The authors' data and materials published in the literature were used to obtain analytical approximations for the boundaries of the stability fields of monosulfide solid solution (mss), pentlandite solid solution (pn), and, partly, heazlewoodite solid solution (hzss) in the concentration triangle at 873 K. This made it possible to quantitatively describe the isothermal section of the phase diagram of the Fe-FeS-NiS-Ni system. The pyrrhotite technique was employed to measure the sulfur fugacity f(S-2) in the section with 48 and 51 at % S and the FeS-Ni3S2 join at this temperature. The dependence of log f(S-2) on composition within the mss stability field was derived from the additive model and approximated data on Fe1-deltaS and Ni1-deltaS. The corresponding equation was used to describe the dependence of log f(S-2) on the composition along the two-phase boundaries between the (mss + pn), (mss + hzss), (mss + tn), and (mss + ka) fields, where tn and ka are the (Fe, Ni) solid solution with gamma-Fe and alpha-Fe structures, respectively. The position of S-2 isobars was evaluated for the (mss + pnss), (mss + hzss), and (mss + tn) binary fields.